2012
DOI: 10.1111/cdoe.12020
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to reliability assessment of dental caries examinations

Abstract: This study highlights the importance of assessing both systematic and random sources of examiner agreement to correctly interpret kappa measures of reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
3
30
0
4
Order By: Relevance
“…Another approach would have been to collapse the current ICDAS scoring system to three or four codes (0, 1‐2, 3‐6 or 0, 1‐2, 3‐4, 5‐6). However, a previous study showed that bias in agreement among examiners was still evident after collapsing the code .…”
Section: Discussionmentioning
confidence: 94%
“…Another approach would have been to collapse the current ICDAS scoring system to three or four codes (0, 1‐2, 3‐6 or 0, 1‐2, 3‐4, 5‐6). However, a previous study showed that bias in agreement among examiners was still evident after collapsing the code .…”
Section: Discussionmentioning
confidence: 94%
“…Research has reported a lack of reliability in detecting early lesions among classification systems used in practice. 34 In addition, the availability of classification factors needed in daily clinical practice are limited in all of these systems. The ADA CCS-with an integrated process for capturing useful components of the caries process-is now available for the next step: initiation of reliability and usability testing by practitioners in clinical and research settings.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…The results of prior studies examining the reliability of caries classification in 2011 and 2013 can offer insight into acceptable limits for agreement in evaluation of the ADA CCS. [34][35] …”
Section: Potential Benefitsmentioning
confidence: 99%
“…In the case of false-positive scores, discoloration and deep-narrow fissures with stain accumulation were involved. This phenomenon has been described as a “typical pitfall” for ICDAS by Altarakehma et al [17]. …”
Section: Discussionmentioning
confidence: 97%
“…Recently, Altarakehma et al [17] and Qudeimat el al. [19] stressed the importance of the contribution of the individual observer to the result.…”
Section: Discussionmentioning
confidence: 99%